Distribution and morphology of sensory and autonomic fibres in the subendocardial plexus of the rat heart. Issue 1 (11th August 2020) - Shenton, Fiona C.; Campbell, Thomas; Jones, James F. X.; Pyner, Susan
Abstract: Cardiac reflexes originating from sensory receptors in the heart ensure blood supply to vital tissues and organs in the face of constantly changing demands. Atrial volume receptors are mechanically sensitive vagal afferents which relay to the medulla and hypothalamus, affecting vasopressin release and renal sympathetic activity. To date, two anatomically distinct sensory endings have been identified which may subserve cardiac mechanosensation: end‐nets and flower‐spray endings. To map the distribution of atrial receptors in the subendocardial space, we have double‐labelled rat right atrial whole mounts for neurofilament heavy chain (NFH) and synaptic vesicle protein 2 (SV2) and generated high‐resolution maps of the rat subendocardial neural plexus at the cavo‐atrial region. In order to elucidate the nature of these fibres, double labelling with synaptophysin (SYN) and either NFH, calcitonin gene‐related peptide (CGRP), choline acetyltransferase (ChAT) or tyrosine hydroxylase (TH) was performed. The findings show that subendocardial nerve nets are denser at the superior cavo‐atrial junction than the mid‐atrial region. Adluminal plexuses had the finest diameters and stained positively for synaptic vesicles (SV2 and SYN), CGRP and TH. These plexuses may represent sympathetic post‐ganglionic fibres and/or sensory afferents. The latter are candidate substrates for type B volume receptors which are excited by stretch during atrial filling. Deeper nerve fibres appeared coarser and may be cholinergic (positive staining for ChAT). Flower‐spray endings were never observed using immunohistochemistry but were delineated clearly with the intravital stain methylene blue. We suggest that differing nerve fibre structures form the basis by which atrial deformation and hence atrial filling is reflected to the brain. Abstract : In search of atrial volume receptors, we performed immunohistochemical characterisation of the subendocardial nerve plexus of the rat right atrium. Rats possess a bicuspid Eustachian valve which is richly innervated. Fine adluminal end‐nets expressed vesicular markers, CGRP and tyrosine hydroxylase. Immunohistochemistry did not label flower‐spray endings but these were identified with methylene blue. The observed plexuses could represent sympathetic post‐ganglionic and/or sensory afferents.